Proximate Analysis of Kijing Taiwan Carcass (Anodonta woodiana) in Wet and Dry Forms - Saiful, Nurrahmi I; Lumenta, Cyska (e-Journal BUDIDAYA PERAIRAN, 2014)
Field practice activities conducted in laboratory incluiding the process of carcass removal from its shells was done in the Laboratory of Nutrition and Fish Feed Technology, and also analysis of Kijing Taiwan carcass chemical composition was done in the Research and Industrial Standardization Institute of Manado. The purpose of field practice are: Analyzing the Proximate composition, Vitamin C, Calcium, and Energy of Kijing Taiwan carcass taiwan in wet and dry form. Providing scientific information about the nutrient content of Kijing Taiwan in wet and dry form. Acquire skills in operating the Proximate instruments of Vitamin C, Calcium, and Energy in the laboratory. Based on the results of the Kijing Taiwan (Anodonta woodiana) carcass proximate analysis Â in wet form, the data showed, 11.59% of protein, 80.66% of water, 0.26% of fat, 3.06% of ash, 0.23% of crude fiber, 4.20% of carbohydrate, 65.5 kcal of energy, 0.59% of calcium, 3.86 mg/100 g of Vitamin C. While the dry form of the data showed, 54.84% of protein, 12.18% of water, 4.08% of fat, 14.92% of ash, 0.53% of crude fiber, 13.45% of carbohydrates, 309.88 kcal of energy, 0.55% of calcium, 14.88% of vitamin C mg/100 g. Keywords: Carcass, Â Anodonta woodiana, proximate analysis, vitamin C, calcium, and energy